lim as t approaches infinity (t^2 + 2)/(t^3 + t^2 -1)?

Would this be 0? Could you show me step by step. I believe we need to divid both top and bottom by the highest power which would be t^3???

### 2 Answers | Add Yours

`lim_(xrarroo) (t^2 + 2)/(t^3 + t^2 -1)`

`= lim_(xrarroo) (t^3(1/t+2/t^2))/((t^3(1+1/t-1/t^3)))`

`= lim_(xrarroo) (1/t+2/t^2)/(1+1/t-1/t^3)`

`= (1/oo+2/oo)/(1+1/oo-1/oo)`

`= (0+0)/(1+0+0)`

`= 0`

So the answer is 0.

`lim_(t->oo)(t^2+2)/(t^3+t^2-1)` `=lim_(t->oo)(t^3+t^2-1)/(t^3+t^2-1)-``lim_(t->oo)(t^3-3)/(t^3+t^2-1)=`

`=lim_(t->oo) 1- (t^3(1-3/t^3))/(t^3(1+1/t-1/t^2))=` `1-lim_(t->oo)(1-3/t^3)/(1+1/t-1/t^2)` `=1-1=0`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes